DEVELOPING A COMMUNICATIVE SUPPLEMENTARY SPEAKING E-BOOK FOR JUNIOR HIGH SCHOOL TEACHERS - Trisnantasari, Ika; Rachmajanti, Sri; Mukminatien, Nur (LET: Linguistics, Literature and English Teaching Journal, 2015)
This research was conducted to develop a communicative supplementary speaking e-book for the English teachers in SMPN 3 Batu. This product provides the communicative speaking materials with communicative tasks to be applied in teaching learning process. The research design of this research is research and development (R & D) that has been modified from Borg and Gall (1983). The instruments used to collect the data for the needs analysis were interview with the teachers and a questionnaire for the students, Â about the current materials. Then the data from the needs analysis used a developing a communicative speaking material product. After that, the product needs to be validated by three experts using validation checklist as the instrument in the expert validation. This product was design for the 8thÂ graders of junior high school, academic year 2013/2014, in SMPN 3 Batu. Twenty students from nine classes that were selected by the teachers were chosen as the subjects of the research. Then the instruments used in try-out were an observation checklist for the studentsâ speaking activity, questionnaire for the students about the try-out material, and observation checklist for the teachers about the try-out material.This e-book contains communicative and interactive speaking materials and tasks to help the teachersâ improve the the studentsâ confidance using English in various communication situations, both formal and informal. This e-bookÂ is also equipped with a manual to help the teachers and the students. Â It revealed that the result of the try-out from the instruments used in this step was very good which means that the developed product did not need any revision.